Greater than the sum: On regulating innovation in electricity distribution networks with externalities - Marques, V. M.; Costa, P. M.; Bento, N. (Utilities Policy, 2022)
To modernise distribution networks and enable the energy transition, we need to understand the most appropriate regulatory approach to incentivise the adoption of technology innovations in the grid. An increasing set of new technologies have positive externalities beyond the provision of basic network activities or improvement of the quality of service. These technologies provide an additional value for the transformation of the grids, challenging traditional regulatory models which tend to overlook the indirect benefits of investments. We develop a decision model to assess firms' incentives to invest in new technologies under different regulatory schemes that consider externality effects. Results show that regulatory schemes, under which companies retain all the losses and gains of achieving (or not) efficiency targets, more effectively promote innovative investments that reduce network costs. However, no one-size-fits-all scheme exist for technologies whose benefits go mostly beyond the network activities, and a case-by-case approach should be preferred.